Management of the Axilla in Early-Stage Breast Cancer: Ontario Health (Cancer Care Ontario) and ASCO Guideline. Issue 27 (20th September 2021) - Brackstone, Muriel; Baldassarre, Fulvia G.; Perera, Francisco E.; Cil, Tulin; Chavez Mac Gregor, Mariana; Dayes, Ian S.; Engel, Jay; Horton, Janet K.; King, Tari A.; Kornecki, Anat; George, Ralph; SenGupta, Sandip K.; et al.
Abstract : PURPOSE: To provide recommendations on the best strategies for the management and on the best timing and treatment (surgical and radiotherapeutic) of the axilla for patients with early-stage breast cancer. METHODS: Ontario Health (Cancer Care Ontario) and ASCO convened a Working Group and Expert Panel to develop evidence-based recommendations informed by a systematic review of the literature. RESULTS: This guideline endorsed two recommendations of the ASCO 2017 guideline for the use of sentinel lymph node biopsy in patients with early-stage breast cancer and expanded on that guideline with recommendations for radiotherapy interventions, timing of staging after neoadjuvant chemotherapy (NAC), and mapping modalities. Overall, the ASCO 2017 guideline, seven high-quality systematic reviews, 54 unique studies, and 65 corollary trials formed the evidentiary basis of this guideline. RECOMMENDATIONS: Recommendations are issued for each of the objectives of this guideline: (1) To determine which patients with early-stage breast cancer require axillary staging, (2) to determine whether any further axillary treatment is indicated for women with early-stage breast cancer who did not receive NAC and are sentinel lymph node–negative at diagnosis, (3) to determine which axillary strategy is indicated for women with early-stage breast cancer who did not receive NAC and are pathologically sentinel lymph node–positive at diagnosis (after a clinically node-negative presentation), (4) to determine what axillary treatment is indicated and what the best timing of axillary treatment for women with early-stage breast cancer is when NAC is used, and (5) to determine which are the best methods for identifying sentinel nodes. Additional information is available at www.asco.org/breast-cancer-guidelines .